Wavelet analysis for polarization maps of networks formed by liquid biological crystals in blood plasma: statistical and fractal approaches - Bachinsky, V.T.; Ushenko, Yu.O.; Tomka, Yu.Ya.; Dubolazov, O.V.; Balanets’ka, V.O.; Karachevtsev, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Considered in this paper are the possibilities of local wavelet analysis for
polarization-inhomogeneous images inherent to blood plasma of healthy and
oncologically ill patients. Determined is the set of statistical, correlation and fractal
parameters for distributions of wavelet coefficients that characterize different scales of
polarization maps inherent to polycrystalline networks of amino-acids in blood plasma.
Established are criteria for differentiation of processes that provide transformation of
birefringent optically-anisotropic structures in blood plasma for various scales of their
geometrical dimensions.